Nutritional status and cardiovascular health in female adolescent elite-level artistic gymnasts and swimmers: A cross-sectional study of 31 athletes - Jakse, Bo.; Jakse, Ba.; Fidler Mis, N.; Jug, B.; Sajber, D.; Godnov, U.; Cuk, I. (Journal of Nutrition and Metabolism, 2021)
Objective. Nutritional status is important for health and competitive achievement. This area remains understudied among elite-level female athletes and is appropriate for research. We examined nutritional status and cardiovascular health markers of two groups of female athletes of the same age and competition period, involved in weight-bearing and a non-weight-bearing sport: gymnasts (n = 17) and swimmers (n = 14); mean age 17.4 and 16.6 years. Methods. Body composition and dietary intake were assessed by bioelectrical impedance and Food Frequency Questionnaire. The concentrations of serum micronutrients (B12, 25-hydroxyvitamin D (25 (OH) D), calcium, magnesium, phosphorus, potassium, and iron), blood lipids, and blood pressure (BP) were measured. Setting and Participants. A cross-sectional study of 31 athletes from Slovenia. Results. Gymnasts had higher body mass index (21.5 vs. 20.1 kg/m2, ) and lower fat free mass (42.4 vs. 46.6 kg, ) than swimmers and comparable body fat percentage (22.5 vs. 22.8%). Both groups had low intake of carbohydrates, fibre, polyunsaturated fats, protein (only gymnasts), and micronutrients (11/13 micronutrients gymnasts and 4/13 swimmers) and high intake of free sugars and saturated fats. Both groups also had significantly lower-than-recommended serum levels of 25 (OH) D. All cardiovascular risk factors were within recommended ranges. Gymnasts had higher LDL cholesterol (2.7 vs. 2.2 mmol/L, ), and swimmers had higher systolic BP (126 vs. 107 mmHg, ). Conclusions. Dietary intake especially in gymnasts was suboptimal, which may reflect in anthropometric and cardiovascular marker differences between gymnasts and swimmers.